2019
DOI: 10.1115/1.4044553
|View full text |Cite
|
Sign up to set email alerts
|

Research and Field Application of the Axial-Torsional Coupled Percussion Drilling Technology

Abstract: Enhancing the rate of penetration (ROP) is one of the goals pursued by the oil and gas drilling industry. It has been proved that percussion drilling is a feasible method to increase drilling efficiency. However, single percussion drilling technology (axial percussion or torsional percussion) cannot cater to the current needs. This paper proposed a new technology/tool called the axial-torsional coupled percussion drilling, which can use the advantages of the percussion drilling in a better way. Mechanical stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Zha et al 16 designed a novel combined percussion jet tool and analyzed its rock-breaking process, and the results show that the percussive tool can produce higher shear stress in rock formations. Mu et al 17 developed an axial-torsional coupled percussive drilling tool and analyzed the tool performance through theoretical calculations, indoor tests, and field tests, and the study results showed that the ROP of the test well could be increased by 1.6-3.3 times after using axial-torsional coupled percussive drilling. Li et al 18 built a numerical method for modeling PDC single cutter-rock impact system and studied the effects on the dynamic rock-breaking mode and rock-breaking performance under the combined action of rotating speed, drilling pressure, alternating impact torque, and alternating impact force.…”
Section: Introductionmentioning
confidence: 99%
“…Zha et al 16 designed a novel combined percussion jet tool and analyzed its rock-breaking process, and the results show that the percussive tool can produce higher shear stress in rock formations. Mu et al 17 developed an axial-torsional coupled percussive drilling tool and analyzed the tool performance through theoretical calculations, indoor tests, and field tests, and the study results showed that the ROP of the test well could be increased by 1.6-3.3 times after using axial-torsional coupled percussive drilling. Li et al 18 built a numerical method for modeling PDC single cutter-rock impact system and studied the effects on the dynamic rock-breaking mode and rock-breaking performance under the combined action of rotating speed, drilling pressure, alternating impact torque, and alternating impact force.…”
Section: Introductionmentioning
confidence: 99%